Transformational Leadership and Perceived Overqualification: A Career Development Perspective - Zhang, Man; Wang, Fan; Weng, Haolin; Zhu, Ting; Liu, Huiyun (Frontiers in Psychology, 2021)
Drawing on social cognitive career theory and a career development perspective, we proposed that supervisor–subordinate guanxi will moderate the relationship between transformational leadership and perceived overqualification. We tested this model using three waves of lagged data collected from 351 company employees in the Yangtze River Delta region in China. The results revealed that transformational leadership had an indirect effect on perceived overqualification through career growth opportunities, and supervisor–subordinate guanxi moderated the positive association between transformational leadership and career growth opportunities. In addition, the mediating effect of transformational leadership on perceived overqualification through career growth opportunities was stronger when the level of supervisor–subordinate guanxi was high and weaker when it was low. The implications of the results, the limitations of the study, and directions for future research are discussed.